Dynamics of Rural Growth in Bangladesh : Sustaining Poverty Reduction - World Bank Group (World Bank, Washington, DC, 2016)
The rural economy in Bangladesh has been a powerful source of economic growth and has substantially reduced poverty, especially since 2000, but the remarkable transformation and unprecedented dynamism in rural Bangladesh are an underexplored, underappreciated, and largely untold story. The analysis identifies the key changes occurring in the rural economy, the principal drivers of rural incomes, the implications for policy, and related actions to foster future growth, further reduce poverty, and improve food security and nutrition. A substantial strength of this study is its empirical foundation, consisting of three sets of detailed data on rural households. Two of the datasets are unique in tracking the same set of households for more than two decades. These data make it possible to examine how change is occurring within and among rural households; they shed considerable light on trends that tend to be obscured at more aggregate levels of analysis. Nationally representative surveys and aggregate secondary data provide complementary and contextually rich insights into the household data.